Vulnerability of power distribution utility poles to tsunami bore impacts - Stephens, Max; Xu, Zhonghou; Whittaker, Colin; Wotherspoon, Liam (Journal of Coastal and Hydraulic Structures, 2023)
Recent events have demonstrated that power distribution networks located in low-lying coastal areas are susceptible to damage from tsunami. Utility poles are a critical component of distribution networks as they support overhead power lines. Damage to the poles could therefore compromise the electricity supply to emergency facilities as well as to homes and businesses over large areas. This work quantifies the component-level tsunami vulnerability of common power distribution line utility poles, considering hydro[1]dynamic wave-impact loading effects but neglecting debris impact and scour effects. First, a series of scaled flume experiments were used to identify the relationship between the tsunami wave properties and hydrodynamic loading histories. Next, nonlinear numerical distribution line utility pole models were validated using the experimental data and extended to account for soil-structure interaction effects. Finally, the loading histories from the flume tests were scaled and used in the numerical models to perform an incremental dynamic tsunami analysis on varying pole geometries and loading orientations at prototype scale. The results from this work provide valuable insight into the response of power distribution poles subjected to tsunami attack. This includes validating idealised approaches to determine the expected failure mode(s) based on pole embedment depths and soil properties and providing probabilistic tools capable of estimating damage based on expected tsunami inundation depths.